2018
DOI: 10.1002/slct.201702426
|View full text |Cite
|
Sign up to set email alerts
|

Ready Access to 3‐Substituted Quinoxalin‐2‐ones under Superparamagnetic Nanoparticle Catalysis

Abstract: Fe2O3 superparamagnetic nanoparticles emerged as a productive recyclable heterogeneous catalyst for the cyclization reaction between α‐keto acids and benzene‐1,2‐diamines to produce quinoxalinones as major products and benzimidazoles as minor products. The Fe2O3 nanoparticles displayed higher activity in the synthesis of quinoxalinones than a series of nano catalysts as well as iron‐, copper‐, nickel‐, and cobalt‐based homogeneous catalysts. Moreover, the Fe2O3 nanoparticles was easily recovered by magnetic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
(51 reference statements)
0
5
0
1
Order By: Relevance
“…The synthesis of quinoxalin‐2(1 H )‐ones 2 was first reported by Hinsberg in 1887 by a condensation/cyclization strategy of 3‐ or 4‐methyl‐ o ‐phenylenediamine 1 and α‐ketoacids under thermal conditions [7] . Much more recently, such cyclocondensations were also achieved by biocatalytic processes, [8] heterogeneous catalysis, [9] microwave [8] or ultrasonic [4] irradiation, in deep eutectic solvents [10] and under solvent‐free co‐grinding conditions [11] . In addition to reaction conditions modifications, α‐ketoacids analogues were also investigated including α‐ketoesters 4 , giving lower reaction rates, [12] and α‐keto thioesters 5 [13] (Scheme 1a).…”
Section: Synthesis Of Quinoxalin‐2(1h)‐onesmentioning
confidence: 99%
“…The synthesis of quinoxalin‐2(1 H )‐ones 2 was first reported by Hinsberg in 1887 by a condensation/cyclization strategy of 3‐ or 4‐methyl‐ o ‐phenylenediamine 1 and α‐ketoacids under thermal conditions [7] . Much more recently, such cyclocondensations were also achieved by biocatalytic processes, [8] heterogeneous catalysis, [9] microwave [8] or ultrasonic [4] irradiation, in deep eutectic solvents [10] and under solvent‐free co‐grinding conditions [11] . In addition to reaction conditions modifications, α‐ketoacids analogues were also investigated including α‐ketoesters 4 , giving lower reaction rates, [12] and α‐keto thioesters 5 [13] (Scheme 1a).…”
Section: Synthesis Of Quinoxalin‐2(1h)‐onesmentioning
confidence: 99%
“…214 Shiri et al reported the use of the same catalyst for the green synthesis of pyrrolo[1,2-a]pyrazines via the threecomponent reaction of ethylenediamine, dimethyl acetylenedicarboxylate, and b-nitrostyrene. 215 The reaction between a-keto acids such as 2-oxo-2phenylacetic acid (196) and various aryl-1,2-diamines (33d) produced 3-phenylquinoxalin-2(1H)-one (197) 216 Several attempts were made using a mixture or combination of solvents, and C 6 H 5 -Cl : H 2 O (1.5 : 0.5) was found to be the best condition for the selective synthesis of 197. These catalytic nanoparticles were recovered by magnetic decantation and their activity was maintained up to the ninth catalytic cycle.…”
Section: Fenp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Based on these outcomes, a reaction mechanism was proposed in which initially a condensation reaction between the NH 2 group and the keto carbonyl of the α-keto acid 1 occurs, releasing H 2 O and leading to the imine I that is converted to the zwitterion species II. Recently, Le, Phan, and co-workers 279 have disclosed the synthesis of quinoxalinones 46 through the cyclization reaction between α-keto acids 1 and ortho-phenylenediamine derivatives 110 catalyzed by Fe 2 O 3 nanoparticles. The best reaction conditions were determined to be stirring a mixture of the αketo acid 1 and the o-phenylenediamine (1.5 equiv) in the presence of superparamagnetic Fe 2 O 3 nanoparticles (10 mol %), in a mixture of PhCl and H 2 O (1.5:0.5 v/v) as the solvent at 100 °C for 24 h. Using the optimized reaction conditions, the authors have prepared 13 differently 3-substituted quinoxalinone derivatives 46 in moderate to very good yields.…”
Section: Chemical Reviewsmentioning
confidence: 99%